The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00277-014-2290-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in multiple myeloma: clinical validation of the Mexican-Spanish version of the QLQ-MY20 instrument

Abstract: Health-related quality of life (HRQL) has become an important outcome measurement in hematology. Our aim was to validate the quality of life questionnaire (QLQ)-MY20 instrument in patients with multiple myeloma (MM) in Mexico. The Mexican-Spanish versions of the QLQ-C30 and QLQ-MY20 instruments were applied to patients with MM at a cancer referral centre. Reliability and validity tests were performed. Test-retest was carried out in selected patients. Ninety-eight patients with MM were included in this study. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 26 publications
4
11
0
4
Order By: Relevance
“…Sexual problems in particular were also reported by patients with newly diagnosed disease pretransplantation . The same was observed for financial difficulties, present in newly diagnosed samples, samples with mixed disease stages and studies reporting baseline evaluation of SCT patients . A high prevalence of fatigue was also reported in these studies .…”
Section: Discussionsupporting
confidence: 63%
“…Sexual problems in particular were also reported by patients with newly diagnosed disease pretransplantation . The same was observed for financial difficulties, present in newly diagnosed samples, samples with mixed disease stages and studies reporting baseline evaluation of SCT patients . A high prevalence of fatigue was also reported in these studies .…”
Section: Discussionsupporting
confidence: 63%
“…Cronbach's alpha >0.7 for all the scales except Nausea and vomiting with alpha value 0.356 and cognitive (0.597)…”
Section: Resultsmentioning
confidence: 94%
“…Correlation between item and own scale >0.3 (0.3‐0.7). Good discriminant validity in majority of scales…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this review also reports that a barrier to using patient-reported outcomes (PRO) in clinical practice is the diversity of such instruments. The oncology generic instruments like EORTC QLQ-C30, FACT-G (Stead et al, 1999;Cella et al, 2012) and their disease specific modules, such as EORTC QLQ-MY20, EORTC QLQ-CML24, FACT-Leu (Cocks et al, 2007;Kontodimopoulos et al, 2012;Jones et al, 2013;Efficace et al, 2014;Espinoza-Zamora et al, 2015) which are currently used have been developed and validated to be used in clinical trials. Only one instrument, MYPOS has been recently developed and validated to be used in clinical practice specific for myeloma and Abbreviations: ALL, acute lymphoid leukemia; AML, acute myeloid leukemia; ANHL, aggressive non-Hodgkin lymphoma; CLL, chronic lymphoid leukemia; CML, chronic myeloid leukemia; CVI, content validity index; CVR, content validity ratio; EMA, european medicines agency; EORTC QLQ C-30, european organization for the research and treatment of cancer quality of life questionnaire -core 30; EORTC QLQ MY-20, european organization for the research and treatment of cancer quality of life questionnaire -myeloma 20; EORTC QLQ-CML24, european organization for the research and treatment of cancer quality of life questionnaire -chronic myeloid leukaemia-24; FACT-G, functional assessment of cancer therapy: general; FACT-Leu, functional assessment of cancer therapy: leukemia; FDA, food and drug administration; HL, hodgkin lymphoma; HM, hematological malignancy; HM-PRO, hematological malignancy patientreported outcome measure; HRQoL, health-related quality of life; ICC, intra-class correlation; I-CVI, item-content validity index; INHL, indolent non-Hodgkin lymphoma.…”
Section: Introductionmentioning
confidence: 99%